Employing weak $ψ-φ$ Contraction in Common Coupled Fixed Point Results for Hybrid Pairs of Mappings Satisfying (EA) Property - Bhavana Deshpande; Amrish Handa; Chetna Kothari (International Journal of Mathematics And its Applications, 2015)
We establish some common coupled fixed point theorems for two hybrid pairs of mappings under weak $ψ -φ$ contraction on a non complete metric space, which is not partially ordered. It is to be noted that to find coupled coincidence point, we do not employ the condition of continuity of any mapping involved therein. An example is also given to validate our results.